Shamim Hanafi’s Creative Style of Criticism - Muhammad Shaukat; Dr. Muhammad Khawar Nawazish (Zaban-o-Adab, 2023)
Abstract: Shamim Hanfi was a leading modern Urdu critic, dramatist, poet, translator, literary columnist and a playwright. He is prominently known especially in the field of modern Urdu criticism. He has authored a number of highly regarded books on literary criticism. He was knowledgeable scholar of Urdu, Hindi, English and local languages of India. In this article we try to understand and deal that his critical writings are not only pure critical inscription but his critical technique feels have creative style. In his writings reader assume that he is talking to him. Shamim Hanfi raises questions on new criticism that it has limited itself in literary theories and terms and converts into a silent lingual island. He has profound view that theories should not be the major concern of literary criticism. In all the life, he emphasis and practice such type of literary criticism that has a creative experience, deep sense, historical, cultural, and civilizational synchronization and has the daily common realities of life. He is differ from his other contemporary critics like, Shams-Ur-Rehman Farooqi, Gopi Chand Narang, Kaleem-Uddin Ahmad, Waris Alvi, Ahtasham Hussain, Fazeel Jafri, Intazar Hussain etc. but strongly inspired by Muhammad Hassan Askari. He criticize on different approach and dislike the frequently use of literary theories in literary criticism and abominate to extract meaning from writings and then set on to interpret in some historical, psychological, philosophical, social, Marxist or any other perspective. This article explores his creative style of criticism.